Vehicle Counting and Motion Direction Detection Using Microphone Array - Severdaks, A.; Liepins, M. (Elektronika ir Elektrotechnika, 2013)
This paper describes a method for counting the vehicles and estimating the direction of their motion using three equidistantly spaced microphones. Paper outlines hardware and software design. Algorithm is based on sound delay estimation between microphones. To implement vehicle counting, sound wave arrival angle is calculated from the derived delays. All measurements and tests took place in real traffic flow under different weather conditions. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5400